Assessing Guidance Styles in Upper Secondary Vocational Education: Can Teachers Differentiate on the Basis of Assessed Style? - Eegdeman, Irene; van Klaveren, Chris; Meeter, Martijn (Frontiers in Education, 2020)
Ability grouping has been argued to improve study success because it allows teachers to better tailor their instruction and guidance to the educational needs of students. However, teachers must then be able to assess what to tailor their instruction to. One test, based on the Life-Cycle Theory of Leadership, assesses cognitive skills and personality traits to generate an advice on the optimal guidance style per student. This test was used in an upper secondary vocational education school to group students with the same advised guidance style. We investigated whether students actually prefer the advised guidance style and whether teachers can adapt their guidance to the styles advised for the group. The results indicate that students are somewhat more likely than chance to prefer the advised guidance style. Similarly, teachers are somewhat more likely than chance to correctly identify this guidance style of a class, but they do not adapt their guidance to the advised style even though they were motivated to do so. This suggests that assessment can be used to diagnose guidance styles, but not with sufficient fidelity so that it can be act upon.